3 - Les fondements théoriques des politiques d'ajustement du FMI dans les pays sous-développés - Makhtar DIOUF, (Africa Development, 1985)
An attempt is made in this paper to criticize from the inside IMF adjustment policies in under-developed countries. The paper shows that IMF economists work from theoretical elements drawn from the Neo classical Political Economy. The various approaches to the balance of payments, suggested by the IMF are on the whole complementary. In the background the moneta rist approach prescribes to central banks what should be undertaken: a permanent policy of credit limitation. When in spite of everything the balance of payments remains in the red on account of external shocks and economic policy mistakes, it then becomes necessary to take short-term adjustment measures to cut down the over-all demand (absorption). These are as follows: monetary measures to increase interest rates, devaluation measures, budgetary measures to reduce subsidies to basic commodities, increase of indirect taxes...; which strengthens inflation and works against the restoration of the balance of payments. Such a situation arises out of the very deficiencies in the IMF model: this is a model of economic policy which does not abide by the rule of social equilibrium (people cannot be asked to accept any kind of sacrifice); the model is supported by the «demand-based inflation» theory whereas in under-developed countries inflation is an imported phenomenon; the suggested devaluation cannot foster exports: IMF econo mists neither take into account flexibilities nor delays in adjust ment (Cobweb theorem); the recommended monetary malthusianism (countries in the Franc Zone) rejects the idea that money has an active role in the Economy. The IMF is in fact trying indirectly to turn under-developed countries into market economies. Yet the neo-classical political economy did end up developing a whole theory about public economy and state intervention precisely because of the deficiencies noted in the developed capitalist countries market.